KOMPETENSI, MOTIVASI DAN KEPUASAN YANG BERDAMPAK PADA KINERJA TENAGA KEPERAWATAN - Aloysius Eka Wardaya; Indra Agung Yudistiro (Universitas Muhammadiyah Semarang, 2018)
Standard implementation accredited the version 2012 expected can improve the trust of hospital consumer that have conducted the effort upgrade the service based on patient safety and also will create the efficient and peaceful [job/activity] environment. This research aim to to know the direct influence and indirectly interest variable and motivate to performance of nurse of RSUD Simo Boyolali through satisfaction work. This research take the location at RSUD Simo Boyolali. Data used by primary data [pass/through] the enquette closed. This research use the analyzer in the form of test kuesioner, test the linieritas, analyse the band, test the t, test the F and coefficient determinasi. Result of research menunjukkkan 1) Interest have an effect on the signifikan to satisfaction work nurse RSUD Simo of Sub-Province Boyolali 2) Motivate to have an effect on the signifikan to satisfaction work nurse in RSUD Simo of Sub-Province Boyolali 3) Interest have an effect on the signifikan to nurse performance in RSUD Simo of Sub-Province Boyolali 4) Motivate to have an effect on the signifikan to nurse performance in RSUD Simo of Sub-Province Boyolali 5) Satisfaction work to have an effect on the signifikan to nurse performance in RSUD Simo of Sub-Province Boyolali. Result of test simultaneously second] equation known the level of f value = 45,586 signifikansi 0,000<0,05, inferential so that by together free variable of interest and motivate to influence the performance through the satisfaction work the. total Value R2 equal to its 0,7822 meaning is variable of nurse performance [in] explainable RSUD Simo Sub-Province Boyolali of interest variable, motivate and satisfaction of equal to 78,22% and the rest of equal to 21,78% explained by other variable outside model. Keywords: Kompetensi, Motivasi, Kepuasan, Kinerja